Caffeinated energy drink consumption among Emirati adolescents is associated with a cluster of poor physical and mental health, and unhealthy dietary and lifestyle behaviors: a cross-sectional study - Faris, MoezAlIslam E.; Al Gharaibeh, Fakir; Islam, M. Rezaul; Abdelrahim, Dana; Saif, Eman Rashid; Turki, Eman Ali; Al-Kitbi, Mahra Khalfan; Abu-Qiyas, Salma; Zeb, Falak; Hasan, Hayder; Hashim, Mona S.; Osaili, Tareq M.; et al. (Frontiers in Public Health, 2023)
Consumption of caffeinated energy drinks (CED) has escalated during the last few years, especially among schoolchildren, with evident adverse health sequelae in this critical age group. This study examined the prevalence of CED consumption and its associations with sleep, physical and mental health, and dietary and lifestyle habits among schoolchildren in the United Arab Emirates (UAE). A structured, self-administered online questionnaire was developed and disseminated among schoolchildren aged 14–18, selected from schools of the seven emirates of the UAE. Less than five thousand (N = 4,648) responses were received. A relatively low prevalence of CED consumption (20%) was found among schoolchildren in the UAE. However, those who reported CED consumption were more likely to report unhealthy dietary (skipping breakfast, frequent snacking, and eating fast foods, low fruit, and vegetable intake) and lifestyle behaviors (long screen time, poor sleep health), in addition to poor self-reported mental and physical health, than non-users. CED consumption was significantly and variably associated with multiple sociodemographic factors such as students’ nationality, parental companionship, sex, school type, education level (children’s and parents’), daily allowance, academic performance, screen time, sleep quality parameters, self-reported physical and mental health, and parents’ employment. Sources of knowledge about CED were social media (55%), friends/schoolmates (52%), and family members (52%). Students believed that CED contained sugar (87%), caffeine (69%), artificial flavors (67%), sweeteners (54%), and stimulating components (43%). The majority (70%) of students reported that CED consumption increases the risks for heart disease, diabetes, high blood sugar (65%), addiction (64%), high blood pressure (59%), and obesity (57%). These results offer important insights for health professionals, child health specialists, policymakers, and parents in the UAE regarding adolescents’ attitudes and behaviors toward CED consumption.